Ceramic Waste as a Viable Alternative to Natural Aggregates in Concrete: Workability and Strength Analysis - Saniul H. Mahi (Journal of Civil Engineering, 2025)
superior mechanical performance and long-term durability; yet, its pervasive usage adds to resource depletion and considerable environmental impacts, mainly from cement manufacturing and aggregate extraction. To address these problems, this study studies the inclusion of ceramic waste as a sustainable alternative to natural aggregates in concrete. The purpose was to examine the impact of ceramic waste on workability, compressive strength, and split tensile strength. A total of sixteen concrete mixes were made, comprising one control mix and fifteen mixes with different quantities of ceramic waste as fine and coarse aggregate replacements. The mix design followed a ratio of 1:1.67:2.81 with a water-to-cement ratio of 0.50, targeting a 28-day compressive strength of 20 MPa. Workability was examined using the slump test, while compressive and split tensile strengths were recorded at 7 and 28 days in line with ASTM standards. The experimental data show that partial replacement of fine aggregates at 10–20% and coarse aggregates at around 10% gave optimal mechanical performance, with strength values similar to or above those of the control mix. Higher substitution levels resulted in losses in both workability and strength due to increased porosity and poorer bonding within the interfacial transition zone. Beyond technical performance, the study indicates that mixing ceramic waste into concrete minimizes landfill disposal and conserves natural resources, consistent with circular economy concepts. These results emphasize the potential of ceramic waste as a viable and eco-efficient material for sustainable concrete manufacturing.